Brain and Human Body Modelling 2021 Selected papers presented at 2021 BHBM Conference at Athinoula A. Martinos Center for Biomedical Imaging, Massachusetts General Hospital - Makarov, Sergey; Noetscher, Gregory; Nummenmaa, Aapo (Springer International Publishing : Imprint: Springer, 2023)
This open access book describes modern applications of computational human modelling to advance neurology, cancer treatment, and radio-frequency studies including regulatory, safety, and wireless communication fields. Readers working on any application that may expose human subjects to electromagnetic radiation will benefit from this book's coverage of the latest models and techniques available to assess a given technology's safety and efficacy in a timely and efficient manner. Describes computational human body phantom construction and application; Explains new practices in computational human body modeling for electromagnetic safety and exposure evaluations; Includes a survey of modern applications for which computational human phantoms are critical; This book describes modern applications of computational human modelling. This book is licensed under the terms of the Creative Commons Attribution 4.0 International License http://creativecommons.org/licenses/by/4.0/ which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license and indicate if changes were made. The images or other third party material in this book are included in the book's Creative Commons license, unless indicated otherwise in a credit line to the material. If material is not included in the book's Creative Commons license and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder.